Morphological Diversity of Soft Palate in Nepalese Population: A Retrospective Cephalometric Study - Upadhyaya, Chandan; Neupane, Ichchha; Sapkota, Binam; Srivastava, Shatakshi (Orthodontic Journal of Nepal, 2017)
Introduction: Soft palate is a fibromuscular portion constituting the back of roof of the mouth which is essential for phonation, deglutition, respiration and velopharyngeal competence. Objective: To study various morphologies of soft palate, difference in proportion of each type and their differencesamong gender and agegroups in Nepalese sample. Materials & Method: A retrospective study was conducted on patients seeking orthodontic treatment. 263 lateral cephalograms were classified on the basis of radiographic appearance. Analysis was done using SPSS (version 20.0). Pearson chi square and descriptive statistics were performed and level of significance was set at p<0.05. Result: In the order of occurrence; rat tail type of soft palate was most prevalent followed by leaf type, butt type, straightline, crooked type and S shaped. There was no significant difference between male and female subjects (p=0.338) and through age groups (p=0.998). Conclusion: The study highlights various types of soft palate present in Nepalese sample which will help as a reference for research pertaining to cleft palate/ velopharyngeal closure and in obstructive sleep apnoea syndrome in Nepalese population